2022-RA-1180-ESGO Nonfunctional complications associated with radical hysterectomy. (20th October 2022) - Alonso-Espías, María; Hernández, Alicia; Alonso-García, Marcos; Gracia, Myriam; García-Pineda, Virginia; Siegrist, Jaime; Diestro, María Dolores; Arnedo, Rocío; Zapardiel, Ignacio
Abstract : Introduction/Background: Bladder disfunction is the most frequent complication after radical hysterectomy. However, there are other relevant complications associated with cervical cancer surgery much less reported in literature. The aim of this study was to evaluate the frequency of nonfunctional complications associated to radical procedures and to determine if there is any risk factor associated with their appearance. Methodology: A retrospective study was conducted including consecutive patients diagnosed with early-stage cervical cancer who underwent radical hysterectomy or radical trachelectomy at La Paz University Hospital from January 2005 to December 2019. Data from intraoperative complications, short-term (<30 days after surgery) and long-term (>30 days after surgery) complications were retrospectively collected. A multivariable analysis was performed in order to identify possible predictors of surgical complications. Results: A total of 111 patients were included. Intraoperative complications occurred in 13 (11.7%) women. Multivariable analysis showed there was a greater risk of intraoperative complications if microscopic parametrial involvement was present (at postoperative analysis). 41 (36.9%) patients had any short-term postoperative complication, being urological complications the most frequent ones. 33 (29.7%) patients had any long-term complication, where lymphedema was the most frequent one (20 patients, 18%). Conclusion: Urological complications are the most frequent ones in radical uterine procedures, especially bladder disfunction. However, other complications such as ureteral injury, fistula or lymphedema, are less frequent but also important due to their impact in the quality of life of patients. We found that parametrial involvement in postoperative pathological analysis was associated with higher intraoperative complications, being the most important factor impacting the presence of bladder dysfunction.